Analysis of Gender and School Origin Factors as Determinants of Students' Mathematics Learning Outcomes - Al Ayyubi, Ibnu Imam; Prayetno, Eko; Nurhikmah; Elysa, Ratianarimamy Niriko; Fauziah, Sifa (Noumerico: Journal of Technology in Mathematics Education, 2025)
This study aims to investigate the impact of gender and school origin on mathematics learning outcomes. Specifically, the study will analyze whether there are significant differences in mathematical ability between male and female students, and evaluate whether learning outcomes differ between students from public and private schools. The research was conducted at three different schools: MI Muslimin Bojongranca, MI Muslimin Cipongkor 1, and SDN Pasir Banteng in West Bandung Regency, specifically in grade V. A quantitative approach with an Ex Post Facto method was applied, and the data were analyzed using descriptive and inferential statistics. The results indicate that school origin significantly affects students’ mathematics learning outcomes, with students from MI Muslimin Cipongkor 1 achieving higher average scores compared to those from MI Muslimin Bojongranca. Meanwhile, no significant differences were found between male and female students. The analysis was continued using non-parametric tests. This study recommends that schools enhance the quality of teaching and learning facilities to improve students’ outcomes, and future research may explore other factors influencing mathematics achievement.